2020
DOI: 10.1111/ijcp.13659
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination rates, knowledge, attitudes and behaviours of healthcare workers in Turkey: A multicentre study

Abstract: Aim Influenza vaccination is the most effective method in prevention of influenza disease and its complications. Our study aimed to investigate the rates of vaccination and the behaviors and attitudes against the vaccine in healthcare workers in Turkey. Methods This multicenter national survey is a descriptive study in which 12475 healthcare workers. Healthcare workers were asked to answer the questionnaire consisting of 12 questions via the survey. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
(20 reference statements)
2
17
0
2
Order By: Relevance
“…Most studies looking at HCPs’ perceived risk of contracting vaccine-preventable diseases focused on influenza. While 25–33% of unvaccinated HCPs in studies in Italy 28 and France 29 stated not being vaccinated against influenza because they did not consider themselves at risk of influenza, 38.9–61.2% of HCPs in Turkey 30 and the Netherlands 31 stated accepting the vaccine to reduce their risk of catching flu. One study from Spain also found that on a scale from 1 (total disagreement) to 5 (total agreement), HCPs scored the statement that they are at a higher risk of catching influenza with a median of 2.57 when asked about reasons for refusing vaccination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies looking at HCPs’ perceived risk of contracting vaccine-preventable diseases focused on influenza. While 25–33% of unvaccinated HCPs in studies in Italy 28 and France 29 stated not being vaccinated against influenza because they did not consider themselves at risk of influenza, 38.9–61.2% of HCPs in Turkey 30 and the Netherlands 31 stated accepting the vaccine to reduce their risk of catching flu. One study from Spain also found that on a scale from 1 (total disagreement) to 5 (total agreement), HCPs scored the statement that they are at a higher risk of catching influenza with a median of 2.57 when asked about reasons for refusing vaccination.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, between 16.3–68.7% of HCPs in France, Italy, Switzerland, Germany, and Turkey stated that doubts about influenza vaccine usefulness and importance was a barrier to their own or other HCP vaccination against influenza. 30 , 35 , 43 , 61 , 63 , 68–71 Additionally, a study in Italy found that 59.3% of HCPs missed Hepatitis B vaccination because they believed the vaccine was unnecessary, compared to 10.4% for MMR vaccination and 20.3% for DTP vaccination. 43 …”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in Pakistan revealed that 72.6% of doctors were not aware of the influenza vaccine recommendations and guidelines [ 23 ]. In a comprehensive Turkish study conducted with 12,574 healthcare providers, the rate of regular vaccination was found to be 6.7%, while it was found that 55% of healthcare workers had never had a influenza vaccine [ 24 ]. In a study conducted with healthcare providers, awareness on pneumococcal and influenza vaccines was 58.7% and 86.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In studies, the rate of seasonal influenza vaccination in healthcare workers ranges from 9% to 92%. [10] In a study we assessed the influenza vaccination of 12,475 healthcare workers in our country, while only 6.7% of the healthcare workers were regularly vaccinated 18.8% stated that they were sometimes vaccinated [11] In the study by Kul et al in our country, 371 individuals were questioned about whether they received the influenza vaccine or not and it was found that 134 (36.1%) of the participants were vaccinated at least once in their lifetime. [12] Of the healthcare workers, 20% have an influenza-like disease in the influenza season [13] and more than 41% keep working although they are infected.…”
Section: Discussionmentioning
confidence: 99%